MFA : A Guide to the Collection of the Museum of Fine Arts, Boston. - Gund, Ann & Graham; Rogers, Malcolm; Shallcross Wohlauer, Gilian (Boston : Museum of Fine Arts Boston, 1999)
Kandinsky, Wassily ; Hoffmann, Josef ; Kirchner, Ernst Ludwig ; Kokoschka, Oskar ; Matisse, Henri ; Picasso, Pablo ; Hartley, Marsden ; Stieglitz, Alfred ; O'Keeffe, Georgia ; Bakst, Leon ; Nolde, Emil ; Schiele, Egon ; Stella, Joseph ; Bourke-White, Margaret ; Hopper, Edward ; Sheeler, Charles ; Rauschenberg, Robert ; Goldin, Nan ; Schreckengost, Viktor ; Davis, Stuart ; Sheeler, Charles ; Model, Lisette ; Beckmann, Max ; Dove, Arthur G. ; Hofmann, Hans ; Kline, Franz ; Pollock, Jackson ; Johns, Jasper ; Louis, Morris ; Frankenthaler, Helen ; Warhol, Andy ; Guston, Philip ; Colescott, Robert ; Smith, David ; Dubuffet, Jean ; Richter, Gerhard ; Polke, Sigmar ; Nevelson, Louise ; Maloof, Sam ; Kuramata, Shiro ; Mendini, Alessandro ; Kelly, Ellsworth ; Murray, Elizabeth ; Smith, Kiki ; Hockney, David ; Miyake, Issey
Engels
boek